The Effectiveness of a Dark Septate Endophytic Fungus, Cladophialophora chaetospira SK51, to Mitigate Strawberry Fusarium Wilt Disease and With Growth Promotion Activities - Harsonowati, Wiwiek; Marian, Malek; Surono; Narisawa, Kazuhiko (Frontiers in Microbiology, 2020)
Strawberry Fusarium wilt, caused by the virulent fungus Fusarium oxysporum formae speciales fragariae (Fof) is a devastating soil-borne disease that causes severe production losses worldwide, including Japan. Fof is one of the top 10 fungal pathogens that threaten global crop security, and a method to effectively control this pathogen has yet to be found. This study aimed to investigate the effectiveness of dark septate endophytic (DSE) fungi against Fof to develop an efficient, effective, and environmentally friendly approach to improve plant health and fitness. A total of 19 fungal isolates were assessed, out of which three (SK47, SK48, and SK51) were selected based on their effectiveness in disease suppression in controlled growth chamber conditions using a soil system. Isolates SK47, SK48, and SK51 suppressed disease severity by 85.71, 61.90, and 90.48%, respectively. Molecular identification based on highly conserved small subunit (SSU), internal transcribed spacer (ITS), and large subunit (LSU) nrRNA regions identified these isolates as DSE Exophiala sp., Exophiala pisciphila, and Cladophialophora chaetospira, respectively. The sequences were deposited under accession numbers MN811693–MN811695 in the GenBank database. Notably, our results revealed that isolate C. chaetospira SK51 possessed superior growth promotion activities as well as disease suppression by significantly increased plant growth parameters (shoot and root dry mass, chlorophyll content, flower bud initiation, and number of fruit) in comparison to control plants and other two fungal candidates. Root colonization by C. chaetospira SK51 was visualized, and it was confirmed that the symbiosis with strawberry plants occurred successfully. Our results provide new insights in the application of DSE fungus C. chaetospira SK51 as a biocontrol agent on strawberry plants could promote plant growth, flower bud initiation, and fruit formation. C. chaetospira SK51 exhibited remarkable beneficial traits for the host plant, and it can potentially be applied in the development of new, safe, and effective treatments as an alternative to chemical fertilizers and fungicides for sustainable crop protection.